2021
DOI: 10.3389/fcvm.2021.730654
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Insomnia With Hypertension and Coronary Artery Disease Among Patients With Type 2 Diabetes Mellitus

Abstract: Purpose: This study aimed to determine whether insomnia is associated with hypertension (HBP) and coronary artery disease (CAD) in a hospital-based sample of patients with type 2 diabetes mellitus (T2DM).Methods: Our present study included 354 patients with T2DM. According to the diagnostic criteria of insomnia, the participants were assigned to three groups based on the duration of T2DM and insomnia diagnosis. Patients with T2DM alone were placed in group A; patients with T2DM longer than insomnia were placed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Diabetes type 2 relevance. All relevant is English language 80% were from medical school education [1], [4], [9], [11], [13], [14], [17], [19], [20], [26], [27], [28], [42], [47], [53]., only 20% from nursing education [6], [10], [30], [46] . 1 and 2)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Diabetes type 2 relevance. All relevant is English language 80% were from medical school education [1], [4], [9], [11], [13], [14], [17], [19], [20], [26], [27], [28], [42], [47], [53]., only 20% from nursing education [6], [10], [30], [46] . 1 and 2)…”
Section: Resultsmentioning
confidence: 99%
“…The associations of diabetes type 2 with blood pressure control mean the difference between diabetes type 2 with standard sleep groups. Furthermore, group diabetes type 2 with insomnia was −26.2% (95% CI, 0.12-0.38; p < 0.001), and the mean alteration between diabetes type 2 and insomnia with diabetes type 2 was −32.6% (95% CI, 0.19-0.43; p < 0.001); diabetes type with insomnia and insomnia with diabetes type 2 is no significant difference [9]. Typical variables are associated with a substantial indicator of arterial wall thickening (CA-IMT) REM sleep lateness, age, DM length, systolic blood pressure, and HbA1c as free variables, REM sleep latency (β = −0.232, p = 0.038).…”
Section: The Consequences Of Sleep Deprivation On Blood Pressure Controlmentioning
confidence: 92%
See 2 more Smart Citations
“…In conclusion, the univariate and multivariate logistic regression analysis showed that insomnia was a risk factor for hypertension (univariate: OR = 3.376; 95% CI, 2.290–6.093; P < 0.001; multivariate: OR = 2.832; 95% CI, 1.373–5.841; P = 0.005) and CAD (univariate: OR = 5.019; 95% CI, 3.148–8.001; P < 0.001; multivariate: OR = 5.289; 95% CI, 2.579–10.850; P < 0.001). 44…”
Section: Insomniamentioning
confidence: 99%